Finite element analysis of the wrist joint affected by rheumatoid arthritis - Bajuri, M. N. (Springer Verlag, 2013)
This chapter presents the information on the biomechanical analysis of the rheumatic wrist using the finite element method. This study was designed to better understand the biomechanical behaviour of the diseased wrist, thus assuring better future treatments. The three-dimensional model of the wrist affected by rheumatoid arthritis was constructed from CT images of the healthy volunteer, by considering ten characteristics involving three main symptoms and seven pathophysiology criteria of the disease. Comparison was made between the simulated healthy wrist which functions as control and the rheumatic wrist model. Both models were assigned with the same loading simulating static hand grip action. It was revealed from the finite element analyses that the RA model produced ten times higher contact pressure at the articulations in comparison with the healthy model. Additionally, normal physiological load transfer changed from primarily through the radial side to an increased load transfer of 5 % towards the ulnar. These significant findings recommend that future treatments should be able to avoid any unphysiological impacts as addressed in this study.